Motion-based video representation for scene change detection - NGO, Chong-wah (Institutional Knowledge at Singapore Management University, 2000)
We present a new ly developed scheme for automatical ly partitioning videos into scenes. A scene is general ly referred to as a group of shots taken place in the same site. In this paper, we first propose a motion annotation algorithm based on the analysis of spatiotemporal image volumes. The algorithm characterizes the motions within shots by extracting and analyzing the motion trajectories encoded in the temporal slices of image volumes. A motion-based keyframe computing and selection strategy is thus proposed to compactly represent the content of shots. With these techniques, we further present a scene change detection algorithm by measuring the similarity of the representative keyframes in shots.